MALE STUDENTS' SOCCER SKILLS, MOTIVATION, AND LEARNING ENGAGEMENT THROUGH SHORT VIDEO TECHNIQUES - Fadzilah Abd Rahman; Zhang Zhipeng (International Journal of Accounting, Finance and Business, 2024)
This conceptual study delves into the intricate dynamics surrounding the impact of short video techniques on male students' soccer education in Jiangxi Province, China. This research utilises a complete framework to investigate the interaction between many factors, including the independent variable of short video approaches and the dependent variables of soccer skills, learning motivation, and learning engagement. The conceptual framework visually illustrates the potential pathways through which short video techniques may influence male soccer education experiences. The paradigm considers the mediating functions of learning motivation and engagement while also considering moderating and contextual elements within the specific educational environment of Jiangxi Province. This study contributes to theoretical discourse by bridging innovative pedagogical methods with practical applications in soccer education. Insights from this study have implications for educators, policymakers, and future empirical research. By embracing the potential of short video techniques, educators can enhance soccer skills while nurturing intrinsic motivation and engagement. The significance of this study lies in its ability to guide educational practices and stimulate empirical investigations to validate hypothesised relationships. As male students navigate the realm of soccer education, this paper offers a valuable compass that enriches their learning journey in Jiangxi Province and beyond.